Pengaruh Kreativitas Iklan dan Endorser terhadap Proses Keputusan Pembelian Konsumen Mie Sedaap (Management Analysis Journal, 2014)
The problem in this research is how creativity and endorsers influence the purchase decision process. The purpose of this study was to investigate the influence of advertising creativity and endorser of the purchase decision process. The population in this study is the Faculty of Economics, University of Semarang and consume ever watched an ad Mie Sedaap. The sample usedis determinedby the cluster sampling a total sample of 98 respondents. Methods of data analysis using descriptive analysis and multiple linear regression are in byusing SPSS22. The results showed that simultaneous hypothesis testing and endorser advertising creativity positive and significant impacton the buying decision process. While the partial test results show that advertising creativity positive and significant impacton the buying decision process while the endorser is also positive and significant impacton the buying decision process.The conclusionsin this study is the better creativity the nadvertising will in crease the purchase decision process and the better the endorser is used, it will increase the purchase decision process and the buying decision process would increase if advertising and endorser creativity is also enhanced